Horticultural Farmer Empowerment Strategy Based on Good Agricultural Practices (GAP): an Analytical Hierarchy Process (AHP) Approach - Prajanti, Sucihatiningsih Dian Wisika; Widiatningrum, Talitha; Litaay, Christina; Amelia, Dhea Rizky (Komunitas: International Journal of Indonesian Society and Culture, 2024)
This research aims to develop a Horticultural Farmer Empowerment Strategy Based on Good Agricultural Practices (GAP): an Analytical Hierarchy Process (AHP) Approach. This research took place in Semarang Regency, precisely in Kopeng Village, Getasan Subdistrict, in accordance with the targets and objectives of the research. The research uses primary data and secondary data. Data collection methods in this research are observation, interviews, documentation, and questionnaires. Key persons in this research are academics, government, farmers, communities, community institutions, and business actors. The analytical method used in this research is the Analytical Hierarchy Process (AHP). The research result shows that the priority order of strategies that can be implemented are human resource development, government policy, and institutions. Meanwhile, the order of priority for alternative strategies is sustainable guidance and training for farmers and agribusiness actors in creating business innovations, promotional and marketing training using information and communication technology, and increasing the capacity of farmers and agribusiness actors in the use of tools, production based on renewable technology. The suggestion that can be given in this research is that implementing good agricultural practices requires strong commitment from stakeholders so there is a need for motivation and collaboration between farmers, government, and business actors. The implementation of good agricultural practices needs to be carried out with a consistent strategy so strict supervision is needed.